The effects of trade sanctions and disinvestment by foreign countries and its impact on the South African economy - N. Bhana (South African Journal of Business Management, 1987)
In the event of total trade sanctions South Africa should have no difficulty in countering the ban on mineral exports, especially precious metals. Furthermore, earnings from precious metals are likely to increase in the short term followed by a gradual deterioration of these industries as cheaper substitutes are developed and producers from other countries make inroads into markets vacated by South African producers. In the manufacturing sector South Africa may benefit in the short term through import replacement and a drive towards self-sufficiency. However, in the long term factors such as scarcity of capital, technological obsolescence, disadvantages inherent in the lack of international co-operation and competition, and misallocation of resources would indicate that the cost of evading sanctions is too high. A disinvestment of portfolio investments is likely to cause a major decline in the prices of South African mining shares. A large scale disinvestment by multinational companies and foreign disinvestment of shares are likely to cause restructuring and increased economic concentration in the South African economy.
Keywords: 650